The old media in the new media: a comparative study of the kinetoscope and the virtual reality headset. Issue 1 (2nd January 2019) - Rosas, Vladimir
ABSTRACT: The aim of this article is to trace back specific features from the kinetoscope that can be found in the virtual reality headset. I will propose a critical comparison between these two devices using Francois Albera and Maria Tortajada's framework on moving image artifacts, which categorizes them as: Machinery, Spectator and Representation.